The association of peer pressure and peer affiliation with the health risk behaviors of secondary school students in Hong Kong. (August 2016) - Loke, A.Y.; Mak, Y.W.; Wu, C.S.T.
Abstract: Objective: The aim of this study was to explore the relationship between peer pressure and the health risk behaviors of secondary school students. Study design: Cross-sectional study using a self-completed questionnaire. Methods: Secondary school students in Year 3 were the target population of this study. Information was solicited from students on their perceptions of peer pressure using a questionnaire employing the Peer Pressure Inventory and their involvement in risk behaviors using a modified global school-based student health survey. Results: A total of 840 secondary students from Hong Kong completed the questionnaires. The prevalence of secondary students who had ever smoked was 6.4%, consumed alcohol 39.2%, ever used drugs 0.5%, were sexually active 3.9%, and involved in bullying 20.5%. A higher proportion of secondary students involved in risk behaviors were affiliated with peers who were involved in the same activities: smoking (48.9%), drinking alcohol (86.5%), using drugs (18.2%), engaged in sexual activity (34.5%), and bullying (82.6%). The perception of peer conformity and peer involvement was found to be significantly correlated with the students' health risk behaviors, particularly with regard to smoking, drinking alcohol, and bullying. A logistic regression analysis showed that having friends who are involved in the same risk behaviors is the single most important factor associated with the participation of secondary students in those specific risk behaviors. Conclusions: The results of this study provided a better understanding of the association between peer pressure and the adoption of health behaviors. The development of effective peer-led prevention programs to reduce the uptake of health risk behaviors should therefore be promoted to prevent adolescents from developing serious health problems. Highlights: Peer pressure has been identified as a decisive factor in the involvement of adolescents in various risky behaviors. The involvement of adolescents in smoking, drinking, taking drugs, risky sexual behaviors, and bullying has reached an alarming level. Having friends, especially close friends, who engaged in deviant behaviors greatly influenced students to participate in similar risky behaviors.